Anisotropic grain boundary area and energy distributions in tungsten. (1st March 2022) - Chirayutthanasak, Ooraphan; Sarochawikasit, Rajchawit; Wisitsorasak, Apiwat; Rujisamphan, Nopporn; Frolov, Timofey; Oppelstrup, Tomas; Dangtip, Somsak; Rohrer, Gregory S.; Ratanaphan, Sutatch
Abstract: Describing microstructure evolution in tungsten requires a quantitative description of the anisotropic grain boundary energy. We present a grain boundary energy function for tungsten that specifies the energy of an arbitrary boundary given its five macroscopic crystallographic parameters. A comparison of measured grain boundary areas and the grain boundary energies given by the function at the Σ11, Σ17b, and Σ33a misorientations, which are problematic to determine by measurement or atomistic calculations, reveals inverse correlations that are similar to what have been observed in other metals. Graphical abstract: Image, graphical abstract